Maternal Education Mitigates the Negative Effects of Higher Income on the Double Burden of Child Stunting and Maternal Overweight in Rural Mexico. Issue 5 (5th March 2014) - Leroy, Jef L.; Habicht, Jean-Pierre; González de Cossío, Teresa; Ruel, Marie T.
Abstract: Globally, the rate at which maternal overweight and obesity increase with rising wealth is higher than the accompanying decline in the prevalence of child stunting, resulting in the double burden of malnutrition. The positive association between household wealth and child linear growth is larger in households with a more educated mother. However, whether a similar positive and synergistic association between maternal education and household wealth is observed for maternal body weight is unknown. Our objective was to assess the potential protective role of maternal education in the etiology of the double burden of malnutrition (stunted child with an overweight mother). We used data on 1547 nonpregnant mothers (aged 18–49 y) and their children (aged 0–5 y) collected in a cross-sectional survey in 235 rural communities in southern Mexico. Child height-for-age Z-score and maternal body weight were regressed on household wealth, women's schooling, and the interaction between both, controlling for relevant covariates. A similar model was used for the prevalence of double-burden pairs (stunted child with an overweight mother). In mothers with less than primary school, a doubling in wealth was not associated with improved child's height but was associated with an increase in mother's weight (3.7%, P < 0.01). In mothers who had completed primary school, the reverse was found: a doubling in wealth score was associated with improved child height-for-age Z-score (0.32 SD, P < 0.01) but not with mother's weight. As a result, a 100% increase in wealth among households with less schooled mothers was associated with a 4.5 percentage point increase ( P < 0.05) in double-burden pairs; in households with mothers with primary schooling or more, it was not associated with the occurrence of double-burden pairs. Maternal schooling effectively mitigated the negative effects of household wealth on the prevalence of double-burden households in rural Mexico. Where maternal schooling is low, poverty reduction must be accompanied by effective behavior change communication to prevent child stunting and to protect women from unhealthy weight gain.